A carbide and a method for preparing and using the same

CN122977352APending Publication Date: 2026-10-27INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611120048.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

所述制备方法以现有聚苯乙烯系强酸性离子交换树脂为原料,经过在优化的温度条件下进行预碳化,使之转化为碳球材料,再经过阴离子化使之转化为具有阴离子交换性能的碱性碳材料,这种方法可以解决碳材料无法阴离子化的问题,因为在合理的条件下预碳化的碳球同时具有碳骨架和一定量的苯环活性氢

Benefits of technology

通过对聚苯乙烯系强酸性离子交换树脂进行低温碳化,在把树脂材料碳化的同时保留了一定量的联苯环甚至碳杂环的活性氢,这些活性氢给后续的阴离子化(氯甲基化+胺化)提供了反应位,并提供了氯甲基和胺基的铆接位点,经阴离子化后便得到了具有一定量碱性交换基团的碳材料,材料的碱交换容量可达0.47-1.1mmol/g,材料烘干后遇水不裂不碎,材料润湿后体积膨胀率很小,材料表面亲水,非常适合吸收核素后进行水泥固化,并以作为高比表面弱碱性吸附材料用于离子吸附和目标有机物吸附。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977352A_ABST
    Figure CN122977352A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of carbide and its preparation method and application.The preparation method includes the following steps: (1) polystyrene strong acid ion exchange resin is heated carbonization, and intermediate is obtained;(2) intermediate is anionized, and the carbon material is obtained.The preparation method uses existing polystyrene strong acid ion exchange resin as raw material, is pre-carbonized under optimized temperature condition, is converted into carbon sphere material, and is anionized again, is converted into basic carbon material with anion exchange performance, this method can solve the problem that carbon material cannot be anionized, because carbon sphere pre-carbonized under reasonable conditions has carbon skeleton and a certain amount of benzene ring active hydrogen simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ion exchange materials and porous functional carbon materials preparation technology, and particularly to a carbide, its preparation method and application. Background Technology

[0002] Ion exchange materials are functional materials widely used in many fields such as industrial water treatment, substance purification, ion adsorption, solid acid-base catalysis, and adsorption separation. Common ion exchange materials can be divided into two main categories: organic and inorganic. Organic ion exchangers are further divided into cation exchangers (acidic ion exchangers) and anion exchangers (basic ion exchangers), while basic ion exchangers are further divided into strongly basic and weakly basic ion exchangers. Their preparation method uses divinylbenzene cross-linked polystyrene microspheres as raw materials, which are chloromethylated and then amination. When the resulting amino groups are primary, tertiary, or secondary amines, the material is a weakly basic ion exchanger; when the amino groups are completely methylated to quaternary ammonium groups, a strongly basic ion exchanger is obtained. This type of material is widely used in industrial water softening, radionuclide-containing wastewater treatment, ion adsorption, and the adsorption and separation of natural plant active ingredients. It is also used as a solid basic catalyst in industrial catalytic reactions requiring basic catalysis; for example, the hydration reaction of propylene oxide and ethylene oxide can be successfully catalyzed by a weakly basic resin.

[0003] However, traditional polystyrene basic resins still have certain problems: First, the prepared basic resins are often stored and transported in a 50% wet state, resulting in significant transportation costs due to water consumption. This is mainly because ion exchange resins are prone to structural collapse and micropore damage in a dry state, especially since the porous networks of gel-type or macroporous resins rely on moisture to maintain their three-dimensional configuration. Once completely dry, the resin particles shrink and crack, leading to a decrease in specific surface area, reduced exchange capacity, and even irreversible deactivation. Therefore, to ensure the physical stability and functional effectiveness of the resin, the industry generally uses a wet-based form for packaging, transportation, and sales, and recommends that users prevent dehydration and drying during storage. Therefore, using water-resistant carbon spheres as the main framework of ion exchange resins has certain technical advantages, as this material can be stored and transported in an anhydrous dry state.

[0004] Secondly, for ion adsorption operations in the nuclear industry, alkaline ion exchange resins are often not regenerated after adsorbing ions (often radioactive ions). They are directly dried and then solidified with cement. Since the resin is an organic material, it hinders the contact reaction between cement particles and water. Moreover, the resin absorbs water and expands significantly, often causing cracks in the solidified cement body. This severely restricts the application of alkaline ion exchange resins in the nuclear industry. Therefore, the nuclear industry urgently needs a carbon-based material with ion exchange function that does not absorb water and expand significantly.

[0005] In summary, a carbonaceous material with ion exchange properties is needed in fields such as ion exchange, nuclear industry ion adsorption, and high-temperature resistant solid acid catalysts. This material should possess the skeletal stability and low water absorption and swelling properties of inorganic carbon materials, while also having ion exchange groups.

[0006] However, if readily available activated carbon materials are chosen for anionization to obtain basic ion exchange groups, the skeleton of the activated carbon material is a graphite layer, and its hexagonal carbon ring edges have almost no active hydrogen. The first step of anionization is chloromethylation, which requires active hydrogen on the benzene ring. This makes it difficult to attach chloromethyl groups to the graphite rings of activated carbon, even under stringent chloromethylation conditions. To address this issue, some literature reports high-temperature reduction of activated carbon in a hydrogen atmosphere to graft active hydrogen onto individual graphite rings before proceeding to the next step. However, this method requires a high-temperature reduction reaction in a hydrogen atmosphere, posing a significant risk for industrial application. Furthermore, the benzene ring active hydrogen content of the resulting product remains very low.

[0007] Therefore, how to prepare an alkaline carbon material with good skeletal stability, low water absorption and swelling, and anion exchange properties has become an urgent problem to be solved in this field. Summary of the Invention

[0008] To address the aforementioned technical problems, the present invention aims to provide a carbide, its preparation method, and its application. The preparation method uses existing polystyrene-based strong acid ion exchange resin as raw material. Under optimized temperature conditions, the resin is pre-carbonized to transform it into carbon spheres. Then, it undergoes anionization to convert it into a basic carbon material with anion exchange properties. This method solves the problem of carbon materials being unable to anionize because, under appropriate conditions, the pre-carbonized carbon spheres simultaneously possess a carbon framework and a certain amount of benzene ring active hydrogen.

[0009] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a carbon material, the method comprising the following steps: (1) The polystyrene-based strong acid ion exchange resin is heated and carbonized to obtain an intermediate; (2) The intermediate is anionized to obtain the carbon material.

[0010] In this invention, to address the problems of existing activated carbon materials being difficult to anionize and existing anion exchange resin skeletons being unstable (fragile and prone to water absorption and swelling), this invention uses existing polystyrene strong acid ion exchange resin as raw material. Under inert gas protection, it is first converted into carbon sphere material through low-temperature pre-carbonization, and then anionized to obtain alkaline carbon material with anion exchange properties.

[0011] In this invention, when the polystyrene-based strong acid ion exchange resin is carbonized at low temperature under inert gas protection, the carbon-sulfur bonds linking the sulfonic acid to the benzene ring break. Simultaneously, due to the strong oxidizing property of the sulfonic acid group, a hydrogen atom from the adjacent carbon atom transfers to the sulfonic acid group, ultimately forming a water molecule with the OH group thereon. This causes the sulfonic acid group to decompose into a SO2 molecule and a water molecule, leaving two active carbon atoms with sp2 hybridized unbonded electrons on the benzene ring (e.g., ...). Figure 1 As shown), due to the high reactivity of these carbon atoms, two adjacent benzene rings will connect through the unbonded electrons of the active carbon atoms to form a biphenyl structure (as shown). Figure 2 As shown), at this point, the carbon atoms at positions A and B of the biphenyl both possess active hydrogen and have little steric hindrance, allowing for anionization. Furthermore, considering the sp2 hybridization orbital orientation, the three adjacent benzene rings, each with two unbonded electrons, will connect in pairs to form a terphenyl structure (as shown). Figure 3 As shown in the diagram, at this point, the three carbon atoms A, B, and C on the terphenyl possess both anionizable active hydrogen and minimal steric hindrance, making anionization possible. This is the reason why the pre-carbonized resin in this technical solution can be anionized. Since a large number of benzene rings in the pre-carbonized carbon material inevitably undergo complete carbonization to become carbocyclic rings (losing active hydrogen), the exchange capacity of the basic carbon material obtained in this technical solution is significantly lower than that of polystyrene-based anion exchange resins. However, its exchange capacity is far higher than the exchange capacity achievable through current anionization of activated carbon.

[0012] Preferably, the anionization of the intermediate in step (2) includes the following steps: The intermediate is mixed with a chloromethylating agent to carry out a chloromethylation reaction, thereby obtaining chloromethylated carbon spheres; the chloromethylated carbon spheres are then mixed with an amination agent to carry out an amination reaction, thereby obtaining the carbon material.

[0013] Preferably, the chloromethylating agent includes chloromethyl ether.

[0014] Preferably, the mass ratio of the chloromethylating agent to the intermediate is (2-6):1, for example, it can be 2.5:1, 3:1, 3.5:1, 4:1 or 5:1, and more preferably (2.5-3):1.

[0015] Preferably, the temperature of the chloromethylation reaction is 30-60°C, for example, 35°C, 40°C, 45°C, 50°C or 55°C, and more preferably 40-50°C.

[0016] Preferably, the chloromethylation reaction takes 2-8 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours or 7 hours.

[0017] Preferably, the amination agent includes any one or a combination of at least two of methylamine, dimethylamine, ethylamine, diethylamine, ethanolamine, or N-methylethanolamine.

[0018] In this invention, the basic groups of the carbon materials with anion exchange properties obtained by the preparation method are all weakly basic groups, and it is almost impossible to obtain strong basic groups. The reason is that... Figure 2 and Figure 3 In the biphenyl and terphenyl structures, the polystyrene chains are greatly shortened, resulting in significant steric hindrance. Therefore, it is difficult to provide spatial positions for larger quaternary ammonium groups, and at most, weak basic groups such as primary amines, secondary amines, and tertiary amines can be obtained.

[0019] Preferably, the molar ratio of the amination agent to the chloromethyl groups on the chloromethylated microspheres is (1.3-3.0):1, for example, it can be 1.5:1, 2:1, 2.2:1, 2.5:1 or 2.8:1, etc.

[0020] Preferably, the amination reaction temperature is 40-80°C, for example, 45°C, 50°C, 60°C, 70°C or 75°C, and more preferably 50-70°C.

[0021] Preferably, the amination reaction takes 4-16 hours, for example, 6 hours, 8 hours, 10 hours, 12 hours or 14 hours.

[0022] Preferably, the amination reaction is carried out in a solvent.

[0023] Preferably, the solvent includes methanol, ethanol, or a water-alcohol mixture; Preferably, the water-to-alcohol volume ratio of the water-to-alcohol mixed solvent is 1:(1-3), for example, it can be 1:1.5, 1:1.8, 1:2, 1:2.3 or 1:2.5, etc.

[0024] Preferably, the alcohol in the aqueous alcohol mixture includes methanol or ethanol.

[0025] Preferably, the volume ratio of the solvent to the chloromethylated carbon spheres is (4-8):1, for example, it can be 5:1, 5.5:1, 6:1, 6.5:1 or 7:1, etc.

[0026] Preferably, the polystyrene-based strong acid ion exchange resin includes macroporous ion exchange resin and / or gel-type ion exchange resin.

[0027] Preferably, the acid exchange capacity of the polystyrene-based strong acid ion exchange resin is 2.5-5 mmol / g, for example, it can be 3 mmol / g, 3.5 mmol / g, 4 mmol / g, 4.5 mmol / g or 4.8 mmol / g, etc.

[0028] Preferably, the polystyrene-based strong acid ion exchange resin includes any one or a combination of at least two of D006, D008, or KC122C.

[0029] Preferably, the heating and carbonization temperature is 250-600℃, for example, it can be 300℃, 350℃, 400℃, 450℃, 500℃ or 550℃, and more preferably 350-550℃.

[0030] In this invention, by controlling the carbonization temperature within the aforementioned range, carbides with high weak base exchange capacity and low water swelling rate in dry ball packed beds can be obtained. If the carbonization temperature is too low, the weak base exchange capacity is low and the water swelling rate is high; if the carbonization temperature is too high, the weak base exchange capacity will also be reduced.

[0031] Preferably, the heating and carbonization time is 0.5-4 h, for example, it can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h or 3.5 h, and more preferably 1-2 h.

[0032] Preferably, the heating and carbonization is carried out under the protection of an inert gas.

[0033] Preferably, the inert gas includes any one or a combination of at least two of nitrogen, helium, argon or carbon dioxide, with nitrogen or carbon dioxide being more preferred.

[0034] In a second aspect, the present invention provides a carbide prepared by the preparation method described in the first aspect.

[0035] Thirdly, the present invention provides an application of the carbide as described in the second aspect in anion exchange.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects: By performing low-temperature carbonization on polystyrene-based strong acid ion exchange resin, a certain amount of active hydrogen from biphenyl rings and even carbon heterocycles is retained while the resin material is carbonized. These active hydrogens provide reaction sites for subsequent anionization (chloromethylation + amination) and provide bonding sites for chloromethyl and amino groups. After anionization, a carbon material with a certain amount of basic exchange groups is obtained. The basic exchange capacity of the material can reach 0.47-1.1 mmol / g. The material does not crack or break when exposed to water after drying, and the volume expansion rate after wetting is very small. The surface of the material is hydrophilic, making it very suitable for cement curing after absorbing nuclides. It can be used as a high specific surface area weak basic adsorbent material for ion adsorption and target organic adsorption. Attached Figure Description

[0037] Figure 1 Diagram showing the thermal decomposition mechanism of sulfonic acid groups on the benzene ring; Figure 2 The mechanism diagram for the formation of biphenyl by connecting two adjacent benzene rings containing two sp2 unbonded carbon atoms (where carbon sites A and B are anionizable sites of the carbon material). Figure 3 The mechanism diagram for the formation of terphenyl by connecting three adjacent benzene rings containing two sp2 unbonded carbon electrons (where the three carbon atom sites A, B, and C are the anionizable sites of the carbon material); Figure 4 The image shows a scanning electron microscope image of the carbon material obtained in Example 1. Figure 5 This is a scanning electron microscope image of the carbon material obtained in Example 2; Figure 6 This is a scanning electron microscope image of the carbon material obtained in Example 3; Figure 7 This is a scanning electron microscope image of the carbon material obtained in Example 4; Figure 8 This is a scanning electron microscope image of the carbon material obtained in Example 5; Figure 9 This is a scanning electron microscope image of the carbon material obtained in Example 6; Figure 10 This is a scanning electron microscope image of the carbon material obtained in Example 7; Figure 11 This is a scanning electron microscope image of the carbon material obtained in Example 8; Figure 12 This is a scanning electron microscope image of the carbon material obtained in Example 9; Figure 13 This is a scanning electron microscope image of the carbon material obtained in Example 10; Figure 14 This is a scanning electron microscope image of the carbon material obtained in Example 11; Figure 15 This is a scanning electron microscope image of the carbon material obtained in Example 12; Figure 16 This is a scanning electron microscope image of the carbon material obtained in Example 13; Figure 17 This is a flowchart of the technical solution. Detailed Implementation

[0038] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0039] Example 1 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 4.5 mmol / g, and carbonize it at 250℃ under N2 protection for 1 hour to obtain 32.3 g of black spherical carbon material intermediate. Add chloromethyl ether at twice the mass of the intermediate and react at 30°C for 8 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount 1.2 times the chlorine content of the carbon spheres. Methanol was selected as the solvent, with a volume 4 times the volume of the carbon spheres. The reaction temperature was 40℃, and the reaction time was 16 hours. The product carbon spheres were thoroughly washed and dried to obtain 33.48 g of carbon spheres with ion exchange properties, which is the carbon material mentioned above.

[0040] Scanning electron microscope images of carbon material particles are shown below. Figure 4 The sample exhibits good sphericity and a weak base exchange capacity of 0.47 mmol / g. The relatively low base exchange capacity is attributed to the residual sulfonic acid groups (approximately 1.89 mmol / g) in the carbon spheres obtained after carbonization of D006 resin at 250°C. These acidic groups interfere with subsequent anionization reactions, resulting in a lower base exchange capacity. However, this material is a composite material possessing both strongly acidic sulfonic acid groups and weakly basic groups. The carbon spheres exhibit good water resistance; pure dry carbon spheres do not crack upon contact with water. Due to the slightly lower degree of carbonization in the first step, the dry carbon spheres have a higher expansion rate, making them less suitable for cement curing operations following ion exchange. However, they are well-suited for use as a non-fragile composite ion exchanger possessing both acidic and basic groups (for the adsorption of ions and target organic matter).

[0041] Example 2 A carbon material and its preparation method. The preparation method includes the following steps: Take 50g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 5 mmol / g, and carbonize it at 300℃ under CO2 protection for 2 hours to obtain 30.1g of black spherical carbon material intermediate. Add 6 times the mass of the intermediate chloromethyl ether and react at 40°C for 2 hours to obtain chloromethylated carbon spheres; Dimethylamine was selected as the amination agent, with a molar amount three times the chlorine content of the carbon spheres. Ethanol was selected as the solvent, with a volume eight times the volume of the carbon spheres. The reaction temperature was 80°C, and the reaction was carried out for 4 hours. The product carbon spheres were thoroughly washed and dried to obtain 31.66g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0042] Scanning electron microscope images of carbon material particles are shown below. Figure 5The sample exhibits good sphericity and a weak base exchange capacity of 0.64 mmol / g. The relatively low base exchange capacity is attributed to the residual sulfonic acid groups (approximately 0.57 mmol / g) in the carbon spheres obtained after carbonization of D006 resin at 300℃. These acidic groups interfere with subsequent anionization reactions, resulting in a lower base exchange capacity. However, this material is a composite material possessing both strongly acidic sulfonic acid groups and weakly basic groups. The carbon spheres exhibit good water resistance; pure dry carbon spheres do not crack upon contact with water. Due to a slightly lower degree of carbonization in the first step, the expansion rate of the dry carbon spheres is slightly higher, making it less suitable for cement curing operations following ion exchange. However, it is well-suited for use as a non-fragmentable composite ion exchanger (for the adsorption of ions and target organic matter).

[0043] Example 3 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 3.5 mmol / g, and carbonize it at 350℃ for 4 hours under Ar gas protection to obtain 25.3 g of black spherical carbon material intermediate. Add 2.5 times the mass of the intermediate chloromethyl ether and react at 60°C for 6 hours to obtain chloromethylated carbon spheres; Dimethylamine was selected as the amination agent, with a molar amount three times the chlorine content of the carbon spheres. The solvent was a 1:1 volume ratio of ethanol to water, with a volume of eight times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction time was 8 hours. The carbon spheres were thoroughly washed and dried to obtain 26.82 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0044] Scanning electron microscope images of carbon material particles are shown below. Figure 6 The carbon spheres exhibit good sphericity and a weak base exchange capacity of 0.77 mmol / g. They also demonstrate good water resistance; pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is at the level of the ion exchange resin's violent decomposition, the resulting product has a high specific surface area, resulting in a relatively pure carbon material. Therefore, the anionized dry carbon spheres have a low expansion rate upon contact with water, making them ideal for cement curing after ion exchange. They are also suitable as a non-fragmentable ion exchanger (for the adsorption of ions and target organic matter). The carbonized carbon spheres still contain 0.11 mmol / g of strong acid groups, thus the material remains a carbon sphere possessing both small amounts of strong acid and weak base groups.

[0045] Example 4 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 2.5 mmol / g, and carbonize it at 400℃ for 1 h under He atmosphere to obtain 25 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Ethanolamine was selected as the amination agent, with a molar amount three times the chlorine content of the carbon spheres. A methanol-water mixture with a volume ratio of 3:1 was selected as the solvent, and the volume of the mixture was eight times the volume of the carbon spheres. The reaction was carried out under reflux at 70°C for 8 hours. The carbon spheres were thoroughly washed and dried to obtain 27.48 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0046] Scanning electron microscope images of carbon material particles are shown below. Figure 7 The carbon spheres exhibit good sphericity. They demonstrate good water resistance; pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is at the level of the ion exchange resin's violent decomposition, the resulting product has a high specific surface area, and the material has become a relatively pure carbon material. The carbonized carbon spheres no longer contain residual strong acid groups (sulfonic acid groups). The anionized dry carbon spheres show extremely low expansion upon contact with water, making them ideal for cement curing operations after ion exchange. They are also suitable for use as a non-fragmentable ion exchanger (for the adsorption of ions and target organic matter).

[0047] Example 5 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 4.5 mmol / g, and carbonize it at 450℃ under N2 protection for 1 h to obtain 24.1 g of black spherical carbon material intermediate. Add 4 times the mass of the intermediate chloromethyl ether and react at 45°C for 8 hours to obtain chloromethylated carbon spheres; N-methylethanolamine was selected as the amination agent, with a molar amount three times the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 2:1, and the volume of the mixture was seven times the volume of the carbon spheres. The reaction temperature was 80°C, and the reaction was carried out for 10 hours. The carbon spheres were thoroughly washed and dried to obtain 27.01 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0048] Scanning electron microscope images of carbon material particles are shown below. Figure 8The sphericity is good. This weakly basic carbon sphere exhibits good water resistance; pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is higher than the temperature at which ion exchange resins decompose violently, the resulting product has a high specific surface area, and the material has become a relatively pure carbon material. The carbonized carbon spheres no longer contain residual strong acid groups (sulfonic acid groups). The anionized dry carbon spheres have extremely low expansion rates upon contact with water, making them very suitable for cement curing operations after ion exchange. They are also suitable for use as a non-fragmentable ion exchanger (for the adsorption of ions and target organic matter).

[0049] Example 6 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 4.5 mmol / g, and carbonize it at 500℃ for 1 h under N2 protection to obtain 23.25 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Ethylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was seven times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction was carried out for 8 hours. The carbon spheres were thoroughly washed and dried to obtain 25.15 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0050] Scanning electron microscope images of carbon material particles are shown below. Figure 9 The sphericity is good. This weakly basic carbon sphere exhibits good water resistance; the pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is higher than the temperature at which the ion exchange resin decomposes violently, the resulting product has a high specific surface area, and the material has become a relatively pure carbon material. The carbonized carbon spheres no longer contain residual strong acidic groups (sulfonic acid groups), and the anionized dry carbon spheres have extremely low expansion rates upon contact with water, making them very suitable for cement curing operations after ion exchange. They are also suitable for use as non-fragmenting ion exchangers (for the adsorption of ions and target organic matter). Due to the high degree of resin carbonization under these conditions, the number of active hydrogen atoms on the benzene rings inside the carbon spheres is reduced, therefore the alkali exchange capacity of the anionized product shows a decreasing trend compared to Example 5.

[0051] Example 7 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 4.5 mmol / g, and carbonize it at 550℃ for 1 h under N2 protection to obtain 23.1 g of black spherical carbon material intermediate. Add chloromethyl ether at 3 times the mass of the carbon spheres and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Diethylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was seven times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction was carried out for 8 hours. The carbon spheres were thoroughly washed and dried to obtain 24.83 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0052] Scanning electron microscope images of carbon material particles are shown below. Figure 10 The sphericity is good. This weakly basic carbon sphere exhibits good water resistance; the pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is higher than the temperature at which the ion exchange resin decomposes violently, the resulting product has a high specific surface area, and the material has become a relatively pure carbon material. The carbonized carbon spheres no longer contain residual strong acid groups (sulfonic acid groups), and the anionized dry carbon spheres have extremely low expansion rates upon contact with water, making them very suitable for cement curing operations after ion exchange. They are also suitable for use as non-fragmenting ion exchangers (for the adsorption of ions and target organic matter). Due to the higher degree of resin carbonization under these conditions, the number of active hydrogen atoms on the benzene rings inside the carbon spheres is reduced, therefore the alkali exchange capacity of its anionized product shows a decreasing trend compared to Example 5.

[0053] Example 8 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based macroporous strong acid ion exchange resin (brand name D006), which has a strong acid ion exchange capacity of 4.5 mmol / g, and carbonize it at 600℃ under N2 protection for 1 h to obtain 22.5 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Dimethylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was seven times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction time was 8 hours. The carbon spheres were thoroughly washed and dried to obtain 24.23 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0054] Scanning electron microscope images of carbon material particles are shown below. Figure 11The sphericity is good. This weakly basic carbon sphere exhibits good water resistance; the pure dry carbon spheres do not crack upon contact with water. Because the carbonization temperature selected for this sample is higher than the temperature at which the ion exchange resin decomposes violently, the resulting product has a high specific surface area, and the material has become a relatively pure carbon material. The carbonized carbon spheres no longer contain any strong acidic groups (sulfonic acid groups) as residues. The anionized dry carbon spheres exhibit extremely low expansion rates upon contact with water, making them very suitable for cement curing operations after ion exchange, and also suitable for use as a non-fragmenting ion exchanger (for the adsorption of ions and target organic matter). Due to the higher degree of resin carbonization under these conditions, the number of active hydrogen atoms on the benzene rings inside the carbon spheres is reduced, resulting in a significantly lower alkali exchange capacity of the anionized product compared to Example 5.

[0055] Example 9 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based gel-type strong acid ion exchange resin (brand name KC122C), which has a strong acid ion exchange capacity of 5 mmol / g, and carbonize it at 350℃ under N2 protection for 2 h to obtain 28.87 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was five times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction was carried out for 8 hours. The product carbon spheres were thoroughly washed and dried to obtain 29.25 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0056] Scanning electron microscope images of carbon material particles are shown below. Figure 12 The weakly basic carbon spheres exhibit good water resistance; the dry carbon spheres do not crack upon contact with water. The specific surface area of ​​this sample cannot be determined using the low-temperature nitrogen adsorption method. Due to the decomposition and carbonization of the sulfonic acid groups at the selected carbonization temperature, the elasticity of the particles decreases while their hardness increases. Furthermore, the gel spheres inherently have few pores, making it difficult for the reactants in the second anionization step to penetrate the particles. This results in a low alkali exchange capacity for the carbon spheres. The dry-based carbon spheres also exhibit low expansion upon contact with water, making them suitable for cement curing operations following ion exchange. They are also well-suited for use as non-fragmentable ion exchangers (for the adsorption of ions and target organic matter).

[0057] Example 10 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based gel-type strong acid ion exchange resin (brand name KC122C), which has a strong acid ion exchange capacity of 4 mmol / g, and carbonize it at 400℃ under N2 protection for 2 h to obtain 26.36 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was five times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction was carried out for 8 hours. The carbon spheres were thoroughly washed and dried to obtain 26.89 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0058] Scanning electron microscope images of carbon material particles are shown below. Figure 13 The carbon spheres exhibit good sphericity. These weakly basic carbon spheres demonstrate good water resistance; the dry carbon spheres do not break upon contact with water. The specific surface area of ​​this sample cannot be determined using low-temperature nitrogen adsorption. Due to significant decomposition of sulfonic acid groups at 400°C, the porosity of the particles increases, resulting in a slightly higher alkali exchange capacity of the obtained carbon sphere product compared to Example 9. However, compared to macroporous resins, gel resins, due to their lack of pores, face greater difficulty in anionization. The dry-based carbon spheres exhibit extremely low swelling upon contact with water, making them suitable for cement curing operations following ion exchange. They are also well-suited for use as non-fragmentable ion exchangers (for the adsorption of ions and target organic matter).

[0059] Example 11 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based gel-type strong acid ion exchange resin (brand name KC122C), which has a strong acid ion exchange capacity of 3 mmol / g, and carbonize it at 450℃ under N2 protection for 2 h to obtain 24.2 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was five times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction time was 8 hours. The carbon spheres were thoroughly washed and dried to obtain 24.6 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0060] Scanning electron microscope images of carbon material particles are shown below. Figure 14The carbon spheres exhibit good sphericity. These weakly basic carbon spheres demonstrate good water resistance; the dry carbon spheres do not break upon contact with water. The specific surface area of ​​this sample cannot be determined using low-temperature nitrogen adsorption. Due to the complete decomposition of sulfonic acid groups at 450°C, the porosity of the particles increases, resulting in a slightly higher alkali exchange capacity of the obtained carbon sphere product compared to Example 9. However, compared to macroporous resins, gel resins, due to their lack of pores, face greater difficulty in anionization. The dry-based carbon spheres exhibit extremely low swelling upon contact with water, making them suitable for cement curing operations following ion exchange. They are also well-suited for use as non-fragmentable ion exchangers (for the adsorption of ions and target organic matter).

[0061] Example 12 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based gel-type strong acid ion exchange resin (brand name KC122C), which has a strong acid ion exchange capacity of 2.5 mmol / g, and carbonize it at 500℃ under N2 protection for 2 h to obtain 22.97 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was five times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction time was 8 hours. The carbon spheres were thoroughly washed and dried to obtain 23.19 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0062] Scanning electron microscope images of carbon material particles are shown below. Figure 15 The sphericity is good. This weakly basic carbon sphere exhibits good water resistance; the pure dry carbon spheres do not break upon contact with water. The specific surface area of ​​this sample cannot be determined by low-temperature nitrogen adsorption. Due to the thorough carbonization of the gel spheres at 500℃, the number of active hydrogen atoms on the benzene rings in the material is greatly reduced, resulting in fewer anionization sites. Therefore, the anion exchange capacity of the product is very low. The dry-based carbon spheres show extremely low swelling upon contact with water, making them suitable for cement curing operations after ion exchange. They are also suitable for use as a non-fragile ion exchanger (for the adsorption of ions and target organic matter).

[0063] Example 13 A carbon material and its preparation method. The preparation method includes the following steps: Take 50 g of dried polystyrene-based gel-type strong acid ion exchange resin (brand name KC122C), which has a strong acid ion exchange capacity of 5 mmol / g, and carbonize it at 550℃ under N2 protection for 2 h to obtain 21.50 g of black spherical carbon material intermediate. Add 3 times the mass of the intermediate chloromethyl ether and react at 50°C for 6 hours to obtain chloromethylated carbon spheres; Methylamine was selected as the amination agent, with a molar amount twice the chlorine content of the carbon spheres. The solvent was a mixture of ethanol and water with a volume ratio of 3:1, and the volume of the mixture was five times the volume of the carbon spheres. The reaction temperature was 70°C, and the reaction time was 8 hours. The carbon spheres were thoroughly washed and dried to obtain 21.6 g of carbon sphere material with ion exchange properties, which is the carbon material mentioned above.

[0064] Scanning electron microscope images of carbon material particles are shown below. Figure 16 The carbon spheres exhibit good sphericity. They also demonstrate good water resistance; pure dry carbon spheres do not crack upon contact with water. The specific surface area of ​​this sample cannot be determined using low-temperature nitrogen adsorption. Due to the complete carbonization of the gel spheres at 550℃, the number of active hydrogen atoms on the benzene rings in the material is extremely low, resulting in very few anion exchange sites; therefore, the anion exchange capacity of the product is very low.

[0065] Example 14 A carbon material and its preparation method differ from Example 8 only in that dimethylamine is replaced with trimethylamine, and the amount of trimethylamine is 1.2 times the chlorine content of the carbon spheres. The base exchange capacity of the product is ≈0.05 mmol / g. This is because the steric hindrance around the biphenyl structure in the sample is very large, making it difficult to provide enough space for the quaternary ammonium group, thus making it difficult to achieve quaternization and obtain a strong base anionic group.

[0066] Test methods (1) Weak base exchange capacity: tested in accordance with national standard GB / T 5760-2000; (2) Sulfonic acid content: The test method shall be in accordance with GB / T 8144-2008; (3) Water swelling rate of dry ball packed bed: The dry ball packed volume is V1. After adding excess water and soaking for 24 hours, the bed volume increases to V2. The water swelling rate is calculated as (V2-V1) / V1×100%; (4) Specific surface area: Detected by low-temperature nitrogen adsorption method.

[0067] The test results are shown in Table 1.

[0068] Table 1 The test results show that: (1) As can be seen from Examples 1-14, the preparation method of the present invention uses existing polystyrene-based strong acid ion exchange resin as raw material. It pre-carbonizes the resin under optimized temperature conditions to convert it into carbon sphere material, and then anionizes it to convert it into basic carbon material with anion exchange properties. This method can solve the problem of carbon materials being unable to anionize, because under reasonable conditions, the pre-carbonized carbon spheres simultaneously possess a carbon skeleton and a certain amount of benzene ring active hydrogen. By further limiting the carbonization temperature, the present invention can obtain carbides with high weak base exchange capacity and low water swelling rate in dry sphere packed beds.

[0069] (2) By comparing Example 1 and Example 14, it can be seen that the present invention improves the performance of the prepared carbide by further limiting the types of amines.

[0070] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a carbon material, characterized in that, The preparation method includes the following steps: (1) The polystyrene-based strong acid ion exchange resin is heated and carbonized to obtain an intermediate; (2) The intermediate is anionized to obtain the carbon material.

2. The preparation method according to claim 1, characterized in that, Step (2) involves anionizing the intermediate, which includes the following steps: The intermediate is mixed with a chloromethylating agent to carry out a chloromethylation reaction, thereby obtaining chloromethylated carbon spheres; the chloromethylated carbon spheres are then mixed with an amination agent to carry out an amination reaction, thereby obtaining the carbon material.

3. The preparation method according to claim 2, characterized in that, The chloromethylating agent includes chloromethyl ether; Preferably, the mass ratio of the chloromethylating agent to the intermediate is (2-6):1, and more preferably (2.5-3):1; Preferably, the temperature of the chloromethylation reaction is 30-60°C, more preferably 40-50°C; Preferably, the chloromethylation reaction takes 2-8 hours.

4. The preparation method according to claim 2 or 3, characterized in that, The amination agent includes any one or a combination of at least two of methylamine, dimethylamine, ethylamine, diethylamine, ethanolamine, or N-methylethanolamine; Preferably, the molar ratio of the amination agent to the chloromethyl groups on the chloromethylated microspheres is (1.3-3.0):1; Preferably, the amination reaction is carried out at a temperature of 40-80°C, more preferably 50-70°C; Preferably, the amination reaction takes 4-16 hours.

5. The preparation method according to any one of claims 1-4, characterized in that, The polystyrene-based strong acid ion exchange resin includes macroporous ion exchange resin and / or gel-type ion exchange resin. Preferably, the polystyrene-based strong acid ion exchange resin has an acid exchange capacity of 2.5-5 mmol / g.

6. The preparation method according to any one of claims 1-5, characterized in that, The temperature for heating and carbonization is 250-600℃, more preferably 350-550℃; Preferably, the heating and carbonization time is 0.5-4 h, more preferably 1-2 h.

7. The preparation method according to any one of claims 1-6, characterized in that, The heating and carbonization is carried out under the protection of an inert gas.

8. The preparation method according to claim 7, characterized in that, The inert gas includes any one or a combination of at least two of nitrogen, helium, argon or carbon dioxide, with nitrogen or carbon dioxide being more preferred.

9. A carbide, characterized in that, The carbide is prepared by the preparation method according to any one of claims 1-8.

10. The application of the carbide as described in claim 9 in anion exchange.